Occupation‐Based Family‐Centered Therapy Approach for Young Children with Feeding Problems in South Korea; A Case Study. (12th August 2013) - An, Sun‐Joung L.; Stein, Franklin; Hwang, Eric
Abstract Documenting the effectiveness of an occupation‐based family‐centered therapy approach, when providing therapy for a young child with feeding problems, is needed in a culture such as Korea, which has a strong medical model of service. A case study was conducted involving a 16‐month‐old boy with feeding problems. An occupation‐based family‐centered therapy approach was carried out for 10 weeks. The results indicated that this approach addressed the physical components of the child's feeding problems and also the parent‐child bonding, which together improved the overall family dynamics. Although these results may stimulate clinicians to consider an alternative approach to a medical model, further research with a larger sample is needed to provide sufficient evidence for therapists to shift to a new service delivery model. Copyright © 2013 John Wiley & Sons, Ltd.